EXPULSIVE HEMORRHAGE AFTER GLAUCOMA FILTERING SURGERY - Jiraskova, Nada; Rozsival, Pavel; Pozlerova, Jana; Ludvikova, Marie; Burova, Mariya (Biomedical papers, 2009)
Aims: To evaluate the incidence, patient risk factors, diagnosis and management of suprachoroidal hemorrhage (SCH) after glaucoma filtering surgery.Methods: Retrospective case series study comprised 1553 eyes having glaucoma filtering surgery during the last 15 years (between January 1993 and December 2007) at our department. Observations included incidence, patient risk factors, peri and postoperative diagnosis, management, and outcomes of SCH after this procedure.Results: Two cases of SCH were revealed. In one eye SCH developed at the end of surgery, in the other eye in the postoperative period. Both patients had systemic and ocular risk factors (hypertension, high preoperative intraocular pressure, myopia, pseudoexfoliation, aphakia or pseudophakia). Visual functions improved in the case of intraoperative SCH over 2 months withouth surgical intervention, in the eye with delayed postoperative SCH visual outcome was poor despite multiple lavages of anterior chamber and vitreous cavity.Conclusion: Suprachoroidal hemorrhage, both expulsive and delayed, is a rare, but severely debilitating complication of glaucoma surgery.
Keywords: Suprachoroidal hemorrhage/Glaucoma filtering surgery/Outcomes